Novel MoS2/C3N5 composites with extended spectral response towards highly efficient photocatalytic abatement of hazardous pollutants. (15th June 2023) - Monga, Divya; Basu, Soumen
Abstract: Carbon nitride materials are one of the potential candidates for photocatalytic application. The present work demonstrates the fabrication of C3 N5 catalyst from a simple, low-cost, and easily available nitrogen-containing precursor, melamine. The facile and microwave mediated method was used to prepare novel MoS2 /C3 N5 composites (referred to as MC) with varying weight ratios (1:1, 1:3, and 3:1). This work provided a novel strategy to improve photocatalytic activity and accordingly fabricated a potential material for effective removal of organic contaminants from water. XRD and FT-IR results affirms the cryatalinity and successful formation of the composites. The elemental composition/distribution was analysed via EDS and color mapping. The elemental oxidation state and successful charge migration in hetrostructure was confirmed by XPS findings. The catalyst's surface morphology indicates tiny MoS2 nanopetals dispersed throughout C3 N5 sheets, while BET studies revealed its high surface area (34.7 m 2 /g). The MC catalysts were highly active in visiblelight, with an energy band gap value of 2.01 eV and a lowered recombination of charges. Because of the strong synergistic relationship (2.19) in the hybrid, excellent activity for methylene blue (MB) dye (88.9%; 0.0157 min −1 ) and fipronil (FIP) photodegradation (85.3%; 0.0175 min −1 ) with MC (3:1) catalyst under visible-light irradiation was obtained. Investigations were carried out on the effect of catalyst quantity, pH, and effectual illumination area on photoactivity. Post-photocatalytic assessment verified the high re-useable character of the catalyst with a high degradation (63% (5 mg/L MB) and 54% (600 mg/L FIP)) after five cycles. The trapping investigations demonstrated that superoxide radicals and holes were intimately enrolled in the degradation activity. Remarkable removal rates of COD (68.4%) and TOC (53.1%) demonstrate excellent photocatalytic removal of practical wastewater even without any preliminary processes. The new study, when paired with previous research, demonstrates the real-world perspective of these novel MC composites for the elimination of refractory contaminants. Graphical abstract: Image 1 Highlights: C3 N5 has been prepared from simple N-containing precursor melamine. MoS2 /C3 N5 composite with different weight-ratio prepared via microwave-route. Effective photodegradation of dyes/pesticide was done under visible light. Catalyst show effective real wastewater degradation with high COD/TOC removal. Catalyst with high efficiency is efficient for wastewater treatment.